Adenylate kinase 7 is a prognostic indicator of overall survival in ovarian cancer. Issue 1 (8th January 2021) - Zhang, Xue-ying; Zhou, Li-li; Jiao, Yan; Li, Yan-qing; Guan, Yi-nuo; Zhao, Yue-chen; Zheng, Lian-wen
Abstract : Abstract: Ovarian cancer (OC), a common malignant heterogeneous gynecological tumor, is the primary cause of cancer-related death in women worldwide. Adenylate kinase (AK) 7 belongs to the adenylate kinase (AK) family and is a cytosolic isoform of AK. Recent studies have demonstrated that AK7 is expressed in several human diseases, including cancer. However, there is a scarcity of reports on the relationship between AK7 and OC. Here, we compared the expression of AK7 in normal and cancerous ovarian tissues from The Cancer Genome Atlas database and used the c 2 test to assess the correlation between AK7 levels and the clinical symptoms of OC. Finally, the prognostic significance of AK7 in OC was determined using the Kaplan–Meier analyses and Cox regression and performed gene set enrichment analysis to detect any relevant signaling pathways. We found that AK7 levels were substantially downregulated in OC than that in normal ovarian tissues ( P  < .001). Low AK7 levels were related to the patients' age ( P  = .0093) in OC. The median overall survival (OS) of patients with low AK7-expressing OC was shorter than patients with high AK7-expressing OC ( P  = .019). The Cox regression analysis (multivariate) identified low AK7 levels were independently related to the prognosis of OC (HR 1.34; P  = .048). Our study demonstrated that the downregulated levels of AK7 could serve as an independent prognostic indicator for the OS in OC. Additionally, gene set enrichment analysis revealed that EMT, apical junction, TGF-b signaling, UV response, and myogenesis were associated in the low AK7 expression phenotype (NOM P  < .05).